cos(x)tan(x) - 2cos(x) + tan(x) - 2 = 0

The first step is to 'group' them such that you can simplify them into two sets:

[cos x tan x + tan x] + [- 2 cos x - 2] = 0

Now simplify each set. Take care with the (-) as it changes the symbol:

tan x(cos x + 1) - 2(cos x + 1) = 0.The common factor is now (cosx+1) so simplify

(cos x + 1)(tanx - 2) = 0. Each factor =0 and so solve each one:

(cos x + 1) = 0

`:.` cos x = -1

`:.` x= 180 degrees + k.360 degrees within the domain 0<x<360

x= 180 degrees k (element of Z)

(tan x - 2) = 0

tan x = 2

x= 63, 43 degrees + k.360 degrees

x= 63,43 degrees k(element of` Z` )

**x= 180 degrees**

**x= 63,43 degrees**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now